Trancing: applying evolution's cognitive adaptation via web art/music. (2017) - Wright, Judson
For whatever reason the prefrontal cortex mutated in our ancestors. Taken in isolation, cortical dominance would easily be a detriment to fitness. Whatever central nervous systems animals without such cortices employ, interpretations of what one senses, and motor schema for reacting are formulated in an unambiguous, monological manner (though we do not claim there need be any 'language of thought'). The trance state is but one means of coordinating conflicting signals from the neocortex ('new brain') and the paleoencephalon ('old brain'). We discuss how trance relates to ritual, and thus to artefact-as-art (both impulses for making and attending thereto). We thus consider the impulse for art, as with hunger or a sex drive, as a means evolution has provided for 'fine tuning' the minds of Homo sapiens.